STRATEGI TERPADU: PERAN DIGITAL MARKETING DAN INFLUENCER MARKETING DALAM MENINGKATKAN PURCHASE INTENTION PADA INDUSTRI E-COMMERCE MELALUI ONLINE CUSTOMER REVIEWS - Saputri, Faola Dwi; Zusrony, Edwin; Sumarlin, Tantik (JURNAL LENTERA BISNIS, 2026)
This study aims to analyze the influence of digital marketing and influencer marketing on consumer purchasing interest with online customer reviews as a mediating variable on e-commerce products. This study uses a quantitative approach with a survey method and involves 80 respondents from the Gen Z group living in Central Java Province aged 20-28 years and selected using a purposive sampling technique. The data analysis technique uses SEM-PLS and is processed using SmartPLS version 4.1.1.4. The results of the study prove that digital marketing and influencer marketing have a positive and significant impact on consumer purchasing interest in e-commerce products. Online customer reviews have a positive impact on purchasing interest and mediate the influence of digital marketing and influencer marketing on purchasing interest in e-commerce products. This finding confirms the importance of digital marketing and influencer marketing in increasing consumer purchasing interest in e-commerce products in the Central Java area.